A new type of oxidized and pre-irradiated micrometeorite. (15th July 2018) - Cordier, Carole; Baecker, Bastian; Ott, Ulrich; Folco, Luigi; Trieloff, Mario
Abstract: This paper investigates the mineralogy and noble gas composition of a unique micrometeorite from the Transantarctic Mountains, #45c.29. The magnetite rim and the particle interior with olivine, pyroxene and magnetite relict grains (30–250 µm in size) set in a vesicular mesostasis are typical features of coarse-grained, partially melted micrometeorites. Particle #45c.29 stands out from other micrometeorites of this type by the texture of the mesostasis made of abundant plagioclase and augite laths, the remarkably high Ni contents in magnetite and olivine relict grains, and by the similarly high abundance of cosmogenic noble gases ( 21 Necos up to 1.62 × 10 −7 cm 3 STP/g and 38 Ar up to 7.2 × 10 −8 cm 3 STP/g). The high Ni content of Fa26 olivine relict grains (NiO ∼ 0.65 wt%), the high Ni (NiO ∼ 0.8 wt%) and Ti (TiO2 ∼ 0.3 wt%) contents of magnetite relicts, and the oxygen isotope composition of a sample of the particle (δ 18 O ∼ 2.3‰, δ 17 O ∼ −1.5‰), suggest a parentage with rare equilibrated CK chondrites. Pyroxene and plagioclase are not expected to crystallize during atmospheric entry of micrometeoroids. Their occurrence in #45c.29 may be explained by the Ca-, Al- and Na- rich composition of its precursor – in agreement with the high abundance of plagioclase reported in the matrix of CK chondrites – if combined with a relatively low cooling rate and, therefore, unusual atmospheric entry parameters (velocity/angle) of the micrometeoroid. Given these specific entry parameters, the particle has recorded unique information on mineralogical and textural transformations of micrometeoroids during atmospheric entry, with solid-state oxidation of the olivine relict grains in the igneous rim, and partial melting of relict mineral phases and relict/melt reactions in the particle interior. The cosmogenic 21 Ne/ 22 Ne ratio of 0.94 ± 0.02 is incompatible with major production by cosmogenic ray irradiation of a small particle in space. We propose that micrometeorite #45c.29 mostly records an earlier irradiation stage, in a meteoroid or more likely near the surface (<20 cm in depth) of an asteroid. In contrast, most of the other unmelted and scoriaceous micrometeorites analyzed for noble gases – if coming from asteroidal sources of the Main Belt – seem to have sampled deeper parts of their parent body, where they were shielded from cosmic rays and from where they were excavated during high-energy disruptive processes.